Li-Fraumeni syndrome in Tunisian carriers with different and rare tumor phenotype: genotype-phenotype correlation - Hela Sassi; Rym Meddeb; Mohamed Aziz Cherif; Chiraz Nasr; Aouatef Riahi; Samia Hannachi; Neila Belguith; Ridha M'rad (BMC, 2022)
Abstract Background Li-Fraumeni syndrome (LFS) is a rare autosomal hereditary predisposition to multiples cancers, mainly affecting young individuals. It is characterized by a broad tumor spectrum. To our best knowledge, only one Tunisian study with a confirmed LFS was published. Methods Our study focused on the clinical, histopathological and genetic results of two patients with rare tumor phenotype and tried to establish genotype-phenotype correlation. The clinical diagnosis was based on Chompret-Bonaiti criteria relative to LFS. Molecular study was assessed using Sanger sequencing of the hotspot germline variants of TP53 gene. Results We report 2 Tunisian families fulfilling the clinical criteria of Chompret-Bonaiti. The tumor phenotype was bilateral breast cancer (BC) in 27-year-old woman and multiple tumors for the second proband, with an onset age of 14, 35 and 36 yo for osteosarcoma, BC and esophageal cancer respectively. Each of them had a rare histological type of breast cancer associated with LFS, phyllode tumor and intralobular carcinoma. Both patients had cancer family history. The molecular study showed deleterious heterozygous germline TP53 variants in each index case: The first had a well-known hotspot missense variation c.742C>T p.(R248W) with a rare histological association, explaining genotype phenotype correlation. The second case had a nonsense variation c.159G>A p.(W53*), rare worldwide, extending the phenotype spectrum in LFS. Immunohistochemistry study in tumor samples confirmed the lack of p53 protein expression. Conclusions Conclusively, germline TP53 testing is primordial in patients with a family history suggestive of LFS for clinical practice avoiding genotoxic treatments and adapting the surveillance. National database in LFS listing clinical and mutational data is important to set, particularly for variants rarely reported worldwide. Experience from different countries must be integrated to harmonize global protocols for cancer surveillance in LFS.